2016
DOI: 10.5815/ijisa.2016.06.01
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Gesture Recognition with Skeletal Data Using Dynamic Time Warping and Nearest Neighbour Classifier

Abstract: Gestures are natural means of co mmun ication between humans, and therefore their application would benefit to many fields where usage of typical input devices, such as keyboards or joysticks is cu mbersome or unpractical (e.g., in noisy environ ment). Recently, together with emergence of new cameras that allow obtaining not only colour images of observed scene, but also offer the software developer rich informat ion on the number of seen hu mans and, what is most interesting, 3D positions of their body parts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 33 publications
1
10
0
2
Order By: Relevance
“…To enhance the gesture recognition accuracy, the appropriate learning algorithms can be selected through the learning algorithm selection module. In a previous study, it was shown that the recognition accuracies of HMMs or RNNs are higher than that of DTW [34][35][36]. Moreover, in our experiment, the highest accuracy was obtained when using HMMs.…”
Section: Gesture Learning Stagesupporting
confidence: 53%
“…To enhance the gesture recognition accuracy, the appropriate learning algorithms can be selected through the learning algorithm selection module. In a previous study, it was shown that the recognition accuracies of HMMs or RNNs are higher than that of DTW [34][35][36]. Moreover, in our experiment, the highest accuracy was obtained when using HMMs.…”
Section: Gesture Learning Stagesupporting
confidence: 53%
“…Reyes et al [8] proposed a feature weighted variation of DTW on 3D joints, using the neck as a reference point. Ribó et al [9] presented a similar approach which relies on DTW, KNN classifiers and some heuristics to improve performance. Ibañez et al [10] used 3D joints and compared DTW with an HMM, acquiring the same precision.…”
Section: Related Workmentioning
confidence: 99%
“…Li [12] utilized information about the angles between extended fingers and a two-stage classification that eliminated gestures with different numbers of detected fingers in the first stage. Plouffe et al [23] proposed a method of comparing data sequences (Dynamic Time Warping -DTW) to static hand posture recognition, although this technique is usually used for the classification of dynamic gestures (e.g., [28]). In [25], the authors developed a system of gesture recognition based on the convex shape decomposition method that uses Morse functions.…”
Section: Related Workmentioning
confidence: 99%